Contribution of implementing K3 aspect to student learning outcomes in class xi PMKR subjects TKR department at SMKN 2 Payakumbuh - Afosma, Pinto Pratama; Putra, Dwi Sudarno; Maulana, Fajar (Research in Education and Technology (REGY), 2023)
This research was a mechanism regarding the Contribution of Implementing Aspects (K3) to student learning outcomes in class XI PMKR Subjects, TKR Department at SMKN 2 Payakumbuh. The application of K3 aspects in vocational high schools has a very big influence on students’ practice learning outcomes, to create maximum learning outcomes, there is an important connection with the application of K3 aspects. This research method was descriptive correlational research which aimed to find out whether there is a relationship between K3 aspects and students’ practical learning outcomes. In addition, to explain the research trial, there is a relationship between the application of occupational safety and health (K3) aspects to students’ vocational learning outcomes. In the trial, several points will be measured later, namely testing the validation of the trial questionnaire and testing the reliability of the questionnaire